Cupping Therapy Improves Quality of Life in Physical Health Aspects of Patients with Hypertension - Anita Yustika Bachtiar (Universitas Muhammadiyah Tangerang, 2021)
Hypertension is the cause of various serious diseases and complications. Symptoms that are often experienced by people with hypertension are headaches, fatigue, chest pain, difficulty sleeping, irritability and irritability even to the point of not being able to work properly and unable to move. These symptoms can affect and even cut quality of life of people with hypertension, especially disruption of physical health aspects. One of the complementary therapies that are widely used by society today is cupping therapy. The purpose of this study was to find the effect of cupping therapy on quality of life of the physical health aspects of hypertension sufferers at Posbindu Wijaya Kusuma in the Special Region of Yogyakarta. This research design is an experimental design with a quasi-random type of experiment (randomized pretest-post test with control group design). The sampling technique used simple random technique to find 16 control groups and 16 experimental groups. Data analysis using Wilcoxon and Mann-Whitney. There was a significant difference quality of life of the respondents' physical health aspects after being given cupping therapy between the intervention group and the control group with a p-value of 0.001 <0.05. There is an effect of cupping therapy on quality of life aspects of the physical health of hypertensive patients. This research expected an alternative for hypertensive patients to improve their quality of life, namely by routinely doing cupping therapy once a month.Keywords: Cupping; Quality of Life; Physical Health; Hypertensionertension.